Diversidad de equinodermos y carpoideos en el Cámbrico Inferior y Medio de la Península Ibérica - Dominguez Alonso, Patricio (Coloquios de Paleontología, 1999)
SEPKOsKI (1987) documentad two pbases of diversification: an initial phase ir tbe Cambrian (named Cambrian Fauna), a second phase during dic Ordovician (namcd Paleozoic-fauna) and a third postulated pbase (the Modern Fauna). SEPKO5KJ included whitin bis Cambrian Fauna inarticulated bracbiopods, trilobites, byolithids, eocrinoids and monoplacophoran molluses. Spanisli Lower Cambrian echinoderms fossit record (Marianense stage) has a very good locality ir where Use (ossus appear articulated and almost to complete in the Saukianda beds. This area is Alanís zone (near Sevilla); (he collected material is basical¡y Gagia (AlaniÁicwstis) andalusiae UBACHS & VIZCAíNo, 1991 and perhaps a second undescribed Gagia. Others invertebrates are archaeocyathids, trilobites, hyolithids an inarticulated brachiopods. The second correspond to the middle Middle Cambrian (Caesaraugustiense stage) and includes a variety of localities as Zafra, Cadenas Ibéricas. Cordillera Cantábrica (Asturias and León). The record has a major diversiíy with many genera: Sotocinetus, Gyrocystis, Progyroc:vsuis, Troc:h.ocysroicles, Asturic-ystis, Elhp-toc-inctus, Ceratocvsris, Eocystires, isolated pIntes and an undescribed stemed eocrinoid (gen. nov.) and Gogia?. From a general point of view this material has a good preservation. We can differenciate two modes of life: 1. sessile forms with ami erected (tihering) aud 2. a lower tiering level detritivoroes vague forms (Caípoids Cincía and Cornuta). The last appear in the Middle Cambrian and were comtemporaneous with the tirst.